Perancangan Interior Smart and Healthy Family Sport Center di Surabaya - Yohana Nathania; Stephanus P. Honggowidjaja (Intra, 2019)
The high level of activities makes people forget to keep their health. To stay healthy, people can start from the daily activities, for example: watch the food he/she consume, regulate diet, rest enough, and do exercise regularly. Exercise is needed for people to keep them healthy and fit. The high level of activity make the family rarely meet each other, so their time to gather with the family is very rare. Nowadays, the exercise facilities are left behind because of some reasons. Giving additional exercise facility can attract the customers to do the exercise, and also give education for healthy lifestyle for society. By the existence of the Interior Family Sport Center Planning can make alive the exercise culture become entrenched in society